MOTIVATION AND VALUES CONTAINED IN THE TAHLILAN TRADITION: - - Bahagia - Bahagia; Abdul Karim Halim; Leny Muniroh; Immas Nurhayati; Rimun Wibowo; Abdul Azis; Muhammad Jamaluddin (Fakultas Agama Islam Universitas Wiralodra Indramayu, 2022)
The objective of this research is to discover tahlilan value in the Muslim community. The method used is qualitative descriptive. Meanwhile, the sampling method used is purposive and data are collected in numerous ways including observation, in-dept-interview, and documentation. The result shows that social value in tahlilan encompasses aiding another individual through distributing food and beverage because when the tahlilan is held, food and beverage are provided to individual who attends tahlilan as well as tahlilan content social value because solidarity among the community is released where the family who undergoes sadness are visited by another person for prying and encourage as well as giving spirit to face grieving circumstances. Additionally, the person who visits tahlilan has the motivation or social motivation where as the person participates in Tahlilan in the public interest rather than individual, in another time when a person experiences the same condition, the community will conduct similar action person. It shows that there is social binding among the community to blend in Tahlilan because social relation which each person have to nurture instead of don’t participate in tahlilan.